Analisis Pengaruh Branding terhadap Produk Kuliner UMKM: Studi Literatur - Habib Rizieq; Ahmad Fathin Fadilah; Fatma Tresno Ingtyas; Laurena Ginting (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study analyzes the influence of branding strategies on the competitiveness of MSME culinary products through a literature study. The study focuses on three main elements, namely brand identity, brand image, and digital branding, which play a role in shaping consumer perception and loyalty in the creative economy era. The research method uses a descriptive qualitative approach with content analysis of academic literature published in 2018–2024. The results of the study show that brand identity functions as a differentiator that strengthens product character, brand image builds consumer trust and loyalty, while digital branding expands the reach of promotions and customer interaction. The synergy between these three elements creates a consistent and sustainable brand experience, thereby strengthening the position of MSME culinary products in the competitive market. This research contributes to the development of integrated branding theory and becomes a practical reference for MSME actors in designing effective branding strategies in the digital era. In addition, the results of this study also emphasize the importance of continuous innovation, the use of social media, and the consistency of brand communication to build strong emotional connections with consumers and increase the added value of local culinary products.